Genome-Wide Analysis of Transposable Elements and Satellite DNAs in Spinacia Species to Shed Light on Their Roles in Sex Chromosome Evolution - Li, Ning; Li, Xiaoyue; Zhou, Jian; Yu, Li’ang; Li, Shufen; Zhang, Yulan; Qin, Ruiyun; Gao, Wujun; Deng, Chuanliang (Frontiers in Plant Science, 2021)
Sex chromosome evolution has mostly been studied in species with heteromorphic sex chromosomes. The Spinacia genus serves as an ideal model for investigating evolutionary mechanisms underlying the transition from homomorphic to heteromorphic sex chromosomes. Among evolutionary factors, repetitive sequences play multiple roles in sex chromosome evolution while their forces have not been fully explored in Spinacia species. Here, we identified major repetitive sequence classes in male and female genomes of Spinacia species and their ancestral relative sugar beet to elucidate the evolutionary processes of sex chromosome evolution using next-generation sequencing (NGS) data. Comparative analysis revealed that the repeat elements of Spinacia species are considerably higher than of sugar beet, especially the Ty3/Gypsy and Ty1/Copia retrotransposons. The long terminal repeat retroelements (LTR) Angela, Athila, and Ogre may be accounted for the higher proportion of repeats in the spinach genome. Comparison of the repeats proportion between female and male genomes of three Spinacia species indicated the different representation in Spinacia tetrandra samples but not in the S. oleracea or S. turkestanica samples. From these results, we speculated that emergence of repetitive DNA sequences may correlate the formation of sex chromosome and the transition from homomorphic sex chromosomes to heteromorphic sex chromosomes as heteromorphic sex chromosomes exclusively existed in Spinacia tetrandra. Three novel sugar beet-specific satellites were identified and confirmed by fluorescence in situ hybridization (FISH); six out of eight new spinach-specific satellites were mapped to the short arm of sex chromosomes. A total of 141 copies of SolSat01-171-s were found in the sex determination region (SDR). Thus, the accumulation of satellite DNA on the short arm of chromosome 1 may be involved in the sex chromosome evolution in Spinacia species. Our study provides a fundamental resource for understanding repeat sequences in Spinacia species and their roles in sex chromosome evolution.